2022
DOI: 10.3390/land11081356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Policy Cognition on the Intention of Villagers’ Withdrawal from Rural Homesteads

Abstract: The Chinese government encourages villagers to withdraw from rural homesteads and puts these homesteads into the land market to revitalize rural homestead resources and make up for the lack of new construction land. Unfortunately, the implementation of the withdrawal from rural homesteads (WRH) policy remains slow. To realize the effective promotion of WRH policy, exploring the impact of policy cognition (PC) on villagers’ WRH intentions has become the key to solving the above problems. Thus, field survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…In addition, subjective norm to behavioral intention is also supported. The results suggest that livelihood capital can promote development right transfer through individual cognition, which is consistent with the effects of attitude to behavior, perceived behavioral control, and subjective norm on behavioral intention in most studies under TPB framework [7,46].…”
Section: Impact Of Livelihood Capital On Behavioral Intention Through...supporting
confidence: 83%
See 4 more Smart Citations
“…In addition, subjective norm to behavioral intention is also supported. The results suggest that livelihood capital can promote development right transfer through individual cognition, which is consistent with the effects of attitude to behavior, perceived behavioral control, and subjective norm on behavioral intention in most studies under TPB framework [7,46].…”
Section: Impact Of Livelihood Capital On Behavioral Intention Through...supporting
confidence: 83%
“…Similar studies have explored the factors that affect farmers' willingness of withdrawal from rural homesteads and rural homestead transfer [7,8]. It was found that both the internal factors and the external environment effect their behavioral intention.…”
Section: Strategies For Improving Behavioral Intentionmentioning
confidence: 97%
See 3 more Smart Citations